![\large\underline{\sf{Solution-}}](https://tex.z-dn.net/?f=%5Clarge%5Cunderline%7B%5Csf%7BSolution-%7D%7D)
![\sf \dfrac{x + 1}{10} - \dfrac{3(x - 1)}{5} = 2](https://tex.z-dn.net/?f=%5Csf%20%5Cdfrac%7Bx%20%2B%201%7D%7B10%7D%20%20-%20%20%5Cdfrac%7B3%28x%20-%201%29%7D%7B5%7D%20%20%3D%202)
![\sf\longmapsto \dfrac{x + 1}{10} - \dfrac{3x - 3}{5} = 2](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20%20%5Cdfrac%7Bx%20%2B%201%7D%7B10%7D%20%20-%20%20%5Cdfrac%7B3x%20-%203%7D%7B5%7D%20%20%3D%202)
![\sf\longmapsto \dfrac{(x + 1) - 2(3x - 3)}{10} = 2](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20%5Cdfrac%7B%28x%20%2B%201%29%20-%202%283x%20-%203%29%7D%7B10%7D%20%20%20%3D%202)
![\sf\longmapsto \dfrac{x + 1 - (6x - 6)}{10} = 2](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20%5Cdfrac%7Bx%20%2B%201%20-%20%286x%20-%206%29%7D%7B10%7D%20%20%3D%202)
![\sf\longmapsto \dfrac{x + 1 - 6x + 6}{10} = 2](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20%20%5Cdfrac%7Bx%20%2B%201%20-%206x%20%2B%206%7D%7B10%7D%20%20%3D%202)
![\sf\longmapsto \dfrac{ - 5x + 7}{10} = 2](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20%5Cdfrac%7B%20-%205x%20%2B%207%7D%7B10%7D%20%20%3D%202)
![\sf\longmapsto - 5x + 7 = 20](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20-%205x%20%2B%207%20%3D%2020)
![\sf\longmapsto - 5x = 20 - 7](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20-%205x%20%3D%2020%20-%207)
![\sf\longmapsto - 5x = 13](https://tex.z-dn.net/?f=%5Csf%5Clongmapsto%20-%205x%20%3D%2013)
![\sf\therefore x = - \dfrac{13}{5}](https://tex.z-dn.net/?f=%5Csf%5Ctherefore%20x%20%3D%20%20-%20%20%5Cdfrac%7B13%7D%7B5%7D%20)
Hence, the value of x will be -13/5 respectively.
Answer:
a. subtract 7 from 10
Step-by-step explanation:
parenthesis goes before everything in this equation
Answer:
D.
Step-by-step explanation:
![\huge \frac{(4 {m}^{2} n)^{2} }{2 {m}^{5}n } \\ \\ \huge= \frac{16 {m}^{4} {n}^{2} }{2 {m}^{5}n } \\ \\ \huge = 8 {m}^{4 - 5} {n}^{2 - 1} \\ \\ \huge \purple{ \boxed{= 8 {m}^{ - 1} n}}](https://tex.z-dn.net/?f=%20%5Chuge%20%5Cfrac%7B%284%20%7Bm%7D%5E%7B2%7D%20n%29%5E%7B2%7D%20%7D%7B2%20%7Bm%7D%5E%7B5%7Dn%20%7D%20%20%5C%5C%20%20%20%5C%5C%20%20%5Chuge%3D%20%20%5Cfrac%7B16%20%7Bm%7D%5E%7B4%7D%20%20%7Bn%7D%5E%7B2%7D%20%7D%7B2%20%7Bm%7D%5E%7B5%7Dn%20%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Chuge%20%3D%208%20%7Bm%7D%5E%7B4%20-%205%7D%20%20%7Bn%7D%5E%7B2%20-%201%7D%20%20%5C%5C%20%20%5C%5C%20%20%20%5Chuge%20%5Cpurple%7B%20%5Cboxed%7B%3D%208%20%7Bm%7D%5E%7B%20-%201%7D%20n%7D%7D)
Answer:
C = 125S + $3750
Step-by-step explanation:
$ 3750 = truck rental; $125 per ton of sugar transported. C is the cost; S is the number of tons transported. The equation relating C to S would be a linear equation like y = mx + b. This equation would be graphed in the first quadrant only. You would start with your y-intercept at (0, 3750). As x increases by 1, your y increases by 125 yielding these points:
(1, 3875) (2, 4000) (3, 4125) etc.
This shows that for each increase by one ton of sugar, the cost goes up $125
Step-by-step explanation:
2 + 3 × 6 + 4 × 3
Here, Parantheses should be put,
<u>(2 + 3) </u>× 6 + 4 × 3. (P.E.D.M.A.S) ( First Parantheses)
= 5 × 6 + 4 × 3 (Then multiplication)
= 30 + 12. (At last addition)
= 42